Executive function and functional and structural brain differences in middle‐age adults with autism spectrum disorder. Issue 12 (21st September 2017) - Braden, B. Blair; Smith, Christopher J.; Thompson, Amiee; Glaspy, Tyler K.; Wood, Emily; Vatsa, Divya; Abbott, Angela E.; McGee, Samuel C.; Baxter, Leslie C.
Abstract : There is a rapidly growing group of aging adults with autism spectrum disorder (ASD) who may have unique needs, yet cognitive and brain function in older adults with ASD is understudied. We combined functional and structural neuroimaging and neuropsychological tests to examine differences between middle‐aged men with ASD and matched neurotypical (NT) men. Participants (ASD, n  = 16; NT, n  = 17) aged 40–64 years were well‐matched according to age, IQ (range: 83–131), and education (range: 9–20 years). Middle‐age adults with ASD made more errors on an executive function task (Wisconsin Card Sorting Test) but performed similarly to NT adults on tests of delayed verbal memory (Rey Auditory Verbal Learning Test) and local visual search (Embedded Figures Task). Independent component analysis of a functional MRI working memory task ( n ‐back) completed by most participants (ASD = 14, NT = 17) showed decreased engagement of a cortico‐striatal‐thalamic‐cortical neural network in older adults with ASD. Structurally, older adults with ASD had reduced bilateral hippocampal volumes, as measured by FreeSurfer. Findings expand our understanding of ASD as a lifelong condition with persistent cognitive and functional and structural brain differences evident at middle‐age. Autism Res 2017, 10: 1945–1959 . © 2017 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: We compared cognitive abilities and brain measures between 16 middle‐age men with high‐functioning autism spectrum disorder (ASD) and 17 typical middle‐age men to better understand how aging affects an older group of adults with ASD. Men with ASD made more errors on a test involving flexible thinking, had less activity in a flexible thinking brain network, and had smaller volume of a brain structure related to memory than typical men. We will follow these older adults over time to determine if aging changes are greater for individuals with ASD.